Impact of Processing Black Soldier Fly (Hermetia illucens) Larvae into Meal on Nutritional Value - Montesqrit, Montesqrit; Harnentis, Harnentis; A, Febriani (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2024)
The objective of this study was to determine the nutritional content of black soldier fly (BSF) maggot meal after undergoing steaming and roasting processes. Steaming was aimed at reducing the crude fat content in the maggot meal, while roasting was intended to accelerate the drying process of fresh maggots. The maggots used in this study were 28-day-old maggots fed with quail manure. The research method employed was an experimental method using a Completely Randomized Design (CRD), consisting of 4 treatments and four replications. The treatments given were: A (maggots not steamed and not roasted), B (maggots not steamed and roasted), C (maggots steamed and not roasted), and D (maggots steamed and roasted). Parameters analyzed included dry matter (%), ash content (%), crude protein (%), and crude fat (%). The results of variance analysis showed that the processing had a very significant effect (P<0.01) on the dry matter, ash content, crude protein, and crude fat content of the resulting maggot meal. The conclusion of this study is that the combined application of steaming and roasting significantly reduced the fat content in maggot meal by up to 87% and increased the protein content by 4%. This processing technique resulted in a product with enhanced quality, extended shelf life, and broader application potential in the feed industry.